Current Teaching Methods Used for English Language Teaching in Upper Elementary School and the Preferred Ones for the Lower Grades - Alhindi, Shereen; Halabi, Maha (Education and Linguistics Research, 2024)
There is no doubt that the teaching method has a significant effect on the student`s outcome and the responsibility for choosing the right method falls on the teacher. With experience, the teacher will be able to decide which method will fit the student’s needs. This research examines the most popular teaching methods and materials for teaching the English language in Saudi public schools, particularly in the upper elementary grades. It also aims to explore the perceptions of English language teachers of the methods and materials they consider to be the most effective in the teaching of lower elementary grades in Saudi public schools, who will be exposed to the English language for the first time. The sample of the study comprised 44 English teachers in Saudi public schools. The findings show that the majority of the English language teachers use Communicative Language Teaching (CLT) either alone or with other teaching methods. Moreover, most of them are willing to use it with the low grades of elementary. The findings also show that the most used materials in the classroom are videos, pictures, audiovisuals and the least used are written texts. These were the same materials that the teachers would like to use (with the same order of preference) for teaching the lower elementary grades. The findings have implications for current English language teachers who are willing to change their way of teaching and future teachers who would benefit from being aware of the effective methods of teaching the elementary grades in particular.